(untitled) (Research, Society and Development, 2025)
Epigenetics plays a fundamental role in regulating biological processes by modulating gene expression without altering the DNA sequence. The manifestation of cardiovascular diseases (CVD) results from the interaction between genetic and environmental factors, such as physical inactivity, inadequate diet, smoking, excessive alcohol consumption, and the use of illicit substances. Among these factors, childhood sedentary behavior stands out as one of the main triggers of epigenetic changes that can directly influence gene expression, contributing to a greater predisposition to developing CVD in adulthood. These alterations affect metabolic, inflammatory, and hormonal pathways, promoting the onset of conditions such as insulin resistance and obesity from childhood. This research is characterized as a qualitative and integrative literature review, aiming to gather, analyze, and synthesize scientific evidence available in the literature on the epigenetic mechanisms associated with sedentary behavior during childhood. Understanding the epigenetic mechanisms involved in this relationship is essential to investigate how early environmental factors negatively impact cardiovascular health throughout life. In this context, the study of epigenetics opens new perspectives in the field of prevention, early diagnosis, prognosis, and the development of more effective personalized therapies tailored to individual needs.